Directional and Spectral Shaping of Light Emission with Mie-Resonant Silicon Nanoantenna Arrays - Vaskin, Aleksandr; Bohn, Justus; Chong, Katie E.; Bucher, Tobias; Zilk, Matthias; Choi, Duk-Yong; Neshev, Dragomir N.; Kivshar, Yuri S.; Pertsch, Thomas; Staude, Isabelle (ACS Photonics, 2018)
We study light emission from square arrays of Mie-resonant silicon nanoantennas situated on a fluorescent glass substrate. When the spectral positions of the silicon nanoantennas' resonances overlap with the intrinsic emission from the glass, the emission is selectively enhanced for certain spectral and spatial frequencies detemined by the design of the nanoantenna array. We measure the emission spectra of the coupled system for a systematic variation of the nanoantenna geometry, showing that the spectral maximum of the emission coincides with the antenna resonance positions observed in linear-optical transmittance spectra. Furthermore, we study the directionality of the emission by back focal plane imaging and numerical calculations based on the Fourier modal method and the reciprocity principle. We observe that the nanoantenna array induces a reshaping of the resonantly enhanced emission in the air half-space into a narrow lobe directed out of the substrate plane. This reshaping is explained by coherent scattering of the emitted light in the nanoantenna array. Our results demonstrate that combining emission enhancement by magnetic dipolar Mie-type resonances of silicon nanoantennas with diffractive coupling in the periodic arrangement allows for the creation of flat light sources with tailored spectral and directional emission properties.
CRIS-Team Scopus Importer:2023-04-20
Keywords: all-dielectric nanophotonics; back focal plane imaging; dielectric nanoantennas; spontaneous emission